Rare case of recurrent cystic mediastinal mass: giant pericardial cyst - Rosita Tanadi, Melina; Dwi Sensusiati, Anggraini (Chulalongkorn Medical Journal, 2025)
Pericardial cysts are unusual benign congenital malformations, with an incidence of 1 per 100,000 individuals. Although considered congenital lesions because of incomplete fusion during embryogenesis, there are other less frequent causes thereof, such as surgery, post-trauma, and inflammatory processes. A pericardial cyst can mimic a malignant mediastinal tumor, cardiac chamber enlargement, or a bronchogenic cyst on a chest X-ray. Most pericardial cysts are asymptomatic until they get bigger, after which they can cause symptoms such as dyspnea, sudden death, and cardiac tamponade, or the cyst may rupture. Radiological imaging plays an important role in ruling out diagnostic conditions, thereby preventing complications. Computed tomography (CT) is the modality of choice for pericardial cysts. Here, we report a case of a 59- year-old female who complained of shortness of breath and cough for 5 days before admission, accompanied by fatigue and nausea. Thoracic CT revealed there was a recurrent giant cystic mediastinal mass in the left hemithorax, and pathological anatomy was suggestive of a pericardial cyst.